Public speaking: view from master’s students in nursing - Faria, Maria de Fátima G.; Fernandes, Silvana Gomes; Pirolo, Sueli Moreira; Silva, Maria Júlia Paes da (Revista da Escola de Enfermagem da USP, 1998)
Communication is a basic element of Nursing; still, speaking in public can be a frightening experience for many nurses. This article intends to study the emotions felt by Master's studentes in Nursing, identifying how they plan their presentation and whatthey consider important enough to reveal to the public. Fifty nurses who were enrolled in the Master's program at EEUSP participated in the study. Data was collected through a questionaire utilizing open-answer questions. Results showed that anxiety was the most frequent emotion related by. them. In the planning of a presentation, however confidence in the content of the speaker's text was the most important aspect, while speaking clearly appeared as the most valued characteristic in general.